Incremental Prognostic Significance of the Elevated Levels of Pentraxin 3 in Patients With Heart Failure With Normal Left Ventricular Ejection Fraction. Issue 4 (10th July 2014) - Matsubara, Junichi; Sugiyama, Seigo; Nozaki, Toshimitsu; Akiyama, Eiichi; Matsuzawa, Yasushi; Kurokawa, Hirofumi; Maeda, Hirofumi; Fujisue, Koichiro; Sugamura, Koichi; Yamamoto, Eiichiro; Matsui, Kunihiko; Jinnouchi, Hideaki; et al.
Abstract : Background: Pentraxin 3 (PTX3) is a novel inflammatory marker produced by various cell types including those of the vasculature and the heart. The relationship between inflammatory markers and prognosis of patients with heart failure with normal ejection fraction (HFNEF) remains unknown. We investigated whether plasma PTX3 levels can predict future cardiovascular events in patients with HFNEF. Methods and Results: Plasma PTX3, high‐sensitivity C‐reactive protein, and B‐type natriuretic peptide levels were measured prospectively in 360 stable patients with HFNEF. The subsequent incidence of cardiovascular events, including cardiovascular death, nonfatal myocardial infarction (MI), unstable angina pectoris, nonfatal ischemic stroke, hospitalization for heart failure decompensation, and coronary revascularization, was determined. During a mean 30‐month follow‐up, 106 patients experienced cardiovascular events. These events were more frequent in patients with high plasma PTX3 levels (>3.0 ng/mL) than low levels (≤3.0 ng/mL). Multivariable Cox hazard analysis showed that PTX3 (hazard ratio: 1.16; 95% CI: 1.05 to 1.27; P <0.01) and B‐type natriuretic peptide (hazard ratio: 1.08; 95% CI: 1.03 to 1.14; P <0.001), but not high‐sensitivity C‐reactive protein levels, were significant predictors of future cardiovascular events. Multivariable Cox analysis with the forced inclusion model, including 5 previously identified prognostic factors, found that PTX3 was a significant predictor of cardiovascular events (hazard ratio: 1.16; 95% CI: 1.06 to 1.27; P <0.01). The C‐statistics for cardiovascular events substantially increased from 0.617 to 0.683 when PTX3 was added to the 5 previously identified prognostic factors. Conclusions: High plasma PTX3 levels, but not other inflammatory markers, are correlated with future cardiovascular events in patients with HFNEF. PTX3 may be a useful biomarker for assessment of risk stratification in HFNEF. Clinical Trial Registration: URL:http://www.umin.ac.jp ; Unique identifier: UMIN000002170.